Construction of intracellular asymmetry and asymmetric division in Escherichia coli - Da-Wei Lin (Nature Portfolio, 2021)
Establishing protein gradients for asymmetric cell division is fundamental across all kingdoms of life. Here the authors construct asymmetric cell division in E. coli by localizing the expression of RNA polymerase using an orthogonal unipolar scaffold, and restricting diffusion of its products.